Nevropsihološka interpretacija Sferičnega zrcala - Žunkovič, Igor (Slavistična revija, 2015)
The article synthesizes scientific knowledge on constructivist elements of Kosovel's poetry proposed by Janez Vrečko in his latest book Constructivism and Kosovel and recent neuroaesthetic discoveries on the working of human perception (Semir Zeki) and on reading perception (Jaana Simola). Kosovel's poem "Spherical Mirror" entails seven constructivist principles and nine constructivist elements. Furthermore, some of them have a specific neuropsychological function. The comparative analysis shows that these neuropsychological functions support and help to construct the meaning of the analyzed poem.
Keywords: "Sferično zrcalo"; branje; constructivism; konstruktivizem; Kosovel, Srečko, 1904-1926; neuropsychological functions; nevropsihološke funkcije; percepcija; perception; reading; Slovene literature; Slovene poets; slovenska književnost; slovenski pesniki